LISTEN: lived experiences of Long COVID: a social media analysis of mental health and supplement use - Martin, Sam; Janse Van Rensburg, Maya; Le, Huong Thien; Firth, Charlie; Chandrasekar, Abinaya; Clark, Sigrún Eyrúnardóttir; Vanderslott, Samantha; Vindrola-Padros, Cecilia; Vera San Juan, Norha (Frontiers in Big Data, 2025)
IntroductionLong COVID, or Post-Acute Sequelae of SARS-CoV-2 infection (PASC), is a complex condition characterized by a wide range of persistent symptoms that can significantly impact an individual's quality of life and mental health. This study explores public perspectives on the mental health impact of Long COVID and the use of dietary supplements for recovery, drawing on social media content. It uniquely addresses how individuals with Long COVID discuss supplement use in the absence of public health recommendations.MethodsThe study employs the LISTEN method (“Collaborative and Digital Analysis of Big Qual Data in Time Sensitive Contexts”), an interdisciplinary approach that combines human insight and digital analysis software. Social media data related to Long COVID, mental health, and supplement use were collected using the Pulsar Platform. Data were analyzed using the free-text discourse analysis tool Infranodus and collaborative qualitative analysis methods.ResultsThe findings reveal key themes, including the impact of Long COVID on mental health, occupational health, and the use of food supplements. Analysis of attitudes toward supplement use highlights the prevalence of negative emotions and experiences among Long COVID patients. The study also identifies the need for evidence-based recommendations and patient education regarding supplement use.DiscussionThe findings contribute to a better understanding of the complex nature of Long COVID and inform the development of comprehensive, patient-centered care strategies addressing both physical and mental health needs.